PENGARUH FASILITAS BELAJAR DAN MEDIA PEMBELAJARAN BERBASIS ICT TERHADAP KEAKTIFAN SISWA DI MASA PANDEMI COVID-19 19 PADA MATA PELAJARAN EKONOMI SMA NEGERI 7 KOTA KEDIRI - B.S., Moh. Alfarizi; Arifin, Zainal; Surindra, Bayu (Universitas Nusantara PGRI Kediri, 2022)
The research is motivated by the results of to determine the effect of learning facilities and ICT based learning media on student activity. The purpose of this stud was to determine (1) there is a positive and significant influence between learning facilities on student activity. (2) there is a positive and significant influence between ICT-based learning media on student activity. (3) there is a positive and significant effect between learning facilities and ICT-based learning media on student activity in economics subjects. This study uses a clause quantitative approach, data collection using a questionnaire/questionnaire. The significant values obtained from the t-test of the independent variable learning facilities and ICT-based learning media on the dependent variable of student activity are as follows 0.000<0.05. With a coefficient of determination (R Square) of 0.460 = 46% which is classified as currently. It concluded that there is an influence of learning facilities and ICT-based learning media on student activity in economics.